Annual and daily pattern of soil temperature in an integrated crop-livestock system in the south of Brazil - Fontana, Denise Cybis; Radin, Bernadete; Oliveira, Guilherme Ari Ferreira de; Belfante Junior, Vlamir; Bremm, Carolina (Agrometeoros, 2024)
Considering the importance of soil temperature and the high spatial and temporal variability associated with soil types, types of vegetation cover, and applied management, this study aimed to determine the daily and annual patterns of soil temperature in a conservation crop-livestock integration system conducted under subtropical climate conditions in the southernBrazil. The experiment was conducted in a crop-livestock integration system cultivated with soybean in the summer and ryegrass in the winter and grazed by sheep. The measured data were NDVI and soil temperature at four depths, with characterization of the annual and daily cycle of the soil profile and daily thermal amplitude, used to calculate the thermal diffusivity. The results showed that the differences in energy availability throughout the seasons, associated with the humid subtropical climate, determines the annual pattern of soil temperature. In summer, the soil profile temperature and daily thermal amplitude are higher than in winter, especially under partial soil cover conditions. Soil thermal diffusivity is low, especially under lower soil moisture conditions, which determines a delay in the time of occurrence of minimum and maximum temperatures in the daily cycle.